Problematizing Immigration Restrictions during COVID-19 in the Social Studies Classroom - William David McCorkle (Research in Social Sciences and Technology, 2020)
In the midst of the COVID-19 pandemic, which affected almost every corner of the globe, nations largely closed their borders and restricted or completely halted immigration. This stance, while understandable, raises questions about how ideas of inclusivity and immigrant rights can be maintained in the midst of chaos and insecurity. This article based in the framework of critical border and migration studies provides an overview of the evolution of immigration policies during the crisis and examines how social studies teachers can problematize assumptions of restrictive immigration policies during times of uncertainty and connect the current situation with past times of crisis. Though this is relevant to teachers from all countries, there is a particular focus on the United States context. Central to the argument is that the ideals of a more open and inclusive immigration system must be maintained even during times of fear and panic. This work builds upon pedagogical scholarship on immigration in the social studies classroom while applying these ideas to the problematic and unique circumstances of immigration during a pandemic.